Automated genre classification in literature - Jordan, Emily (Kansas State University, 2014)
This thesis examines automated genre classification in literature. The approach described uses text based comparison of book summaries to examine if word similarity is a feasible method for identifying genre types. Genres help users form impressions of what form a text will take. Knowing the genre of a literary work provides librarians, information scientists, and other users of a text collection with a summative guide to its form, its possible content, and what its members are about without having to peruse individual topic titles. This makes automatically generating genre labels a potentially useful tool in sorting unmarked text collections or searching the web. This thesis provides a brief overview of the problems faced by researchers wishing to automate genre classification as well as the current work in the field. My own methodology will also be discussed. I implemented two basic methods for labeling genre. The results collected using them will be covered, as well as future work and improvements to the project that I wish to implement.
Keywords: Genre; Automated genre classification; Labeling; Automated; Classification; Computer Science (0984); Library Science (0399)